A formação do formador de leitores em sociedades multiletradas: a leitura como comprometimento do professor de todas as áreas, nos anos finais do ensino fundamental - Almeida, Gizele Cristina Rodrigues Caparroz de (2020)
This research aims at answering some questions related to the development of reading in all basic education subjects, through a context in which the society has become digital and multimodal learners at a fast pace. The main goal of this dissertation is to investigate a group of teachers’ training needs as readers’ educators of multimodal texts at a new standard in a multiliteracy school. Targeting at middle school final years’ teachers, the specific goals of this research are as follows: (1) Investigate how readers of multimodal texts are trained by teachers from all basic education subjects and (2) submit a proposal of continuing in-service training to teachers, in special attention to identifying training needs, taking into account the considerations on reading strategies and multiliteracy practices. The theorical background about the teachers’ continuing in-service training brings the writings of Canário (1998), Imbernón (2010), Marcelo García (2009) and Nóvoa (1991; 1992). The data were collected through an open-ended question questionnaire completed at a private school in Cotia, SP. The teachers responded to the questionnaire reflecting the importance of reading in their lives, the text types they use in their classes (including multimodal texts) and the way reading has been developed in their classes. The data analysis process is based on the methodology of content analysis (BARDIN, 1979). After collecting the teachers’ responses, a continuing in-service training proposal was presented and it aimed at providing them an effective participation in the creation of reading strategies of multimodal genres, in the perspective of multiliteracy, multimodality and multicultularism (ROJO, 2013), meeting the needs of the contemporary society. The Grammar of Visual Design (KRESS; VAN LEEUWEN, 1996), the New London Group’s pedagogy of multiliteracies designing and the studies of Dionísio (2005) and Mayer (2009) bear the teachers’ training proposal. The investigative process of the teachers’ practice, its planning and elaboration, the continuing in-service training proposal and the outcome of its impacts were made using the action research methodology (TRIPP, 2005). The final results obtained in this research reveal the utmost importance, in the immediate context, of a continuing in-service training, targeting the teaching of “ multimodality observation strategies” (PAES DE BARROS, 2009) that embody, in the teaching strategies for reading, the changes of our society, which has become increasingly multimodal and technological